Pemetaan Morfologi Ambang Galala Poka (APG) - Wattimury, Jusuph J; Waas, Harold J.D; Hukubun, Ronald D (Prodi Ilmu Kelautan Fakultas Perikanan dan Ilmu Kelautan Universitas Pattimura, 2023)
The Galala Poka (APG) sill is in the form of an underwater hill located in the narrow waters of the TAD and TAL transition zones. The morphology of APG is important to map because it influences the dynamics of water masses during the tidal period in the TAL and TAD Transitional areas, and can even explain the phenomena of cohesive sediment transport and deposition as well as tidal mixing phenomena that often occur around APG. This research aims to map the topographical profile of the APG seabed and calculate its spatial dimensions.The GIS-based mapping method is used to create an APG seabed topographic model using data compiled from sounding results, digital Navionic Sonar Chart data and digital shipping channel bathymetry data. The trapezoidal rule model is used to calculate the APG dimensions. APG seabed 2D and 3D spatial models mapped with ArcGIS 10.8 and Surfer 23.The results of the analysis found the APG boundaries at coordinates 128.19316 – 128.19829E and 3.66027 – 3.56659S and UTM coordinates 410399.1390 ​​– 410969.1292 mT and 9594764.3000 – 9595384.3000 mU. The topography of APG is generally convex with a flat peak at the center. There are variations in the slope of the seabed, especially on the outer side of the APG. APG volume with a reference depth of 0m (LWS) 1,304,828.05 m3, surface area 151,954.65 m2. At a reference depth of 8m, the APG volume is 20,071.95 m3, the area is 94,887.23 m2. At a reference depth of 10m, the APG volume is 351,296.95 m3, and the surface area is 73,012.06 m2.